Pengaruh Bauran Promosi Terhadap Keputusan Konsumen Dalam Memilih Hotel Pelangi Malang Sebagai Tujuan Menginap (Studi Pada Hotel Pelangi Jalan Merdeka Selatan No 3 Kota Malang) - Sjah, Muhammad Iskandar; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Marketing mix is one of the factors that can influence consumer decisions. Studies on the hospitality marketing mix which consists of eight variables: product, partnership, people, packages, programs, location, promotion, and price to find out how big influence on consumer decisions, the study sample was 60 people. Sampling is done by using a purposive sampling method. While the method of analysis used is multiple linear regression. Regression in order to obtain good results, then prior to the regression test, first tested the validity, reliability testing and test classical assumption of normality test, multicollinearity, heteroscedasticity test. Simultaneous testing to the conclusion that of the eight variables comprising the variable product (X1), cooperation (X2), people (X3), packages (X4), programs (X5), location (X6), promotion (X7), and the price (X8), significantly influence consumer decision Pelangi Hotel Malang. The analysis also showed that only partially promotional variables that have a significant influence on consumer decision Pelangi Hotel Malang. Promotion variable (X7) is the most dominant variable, where the other variables are not significant because the hotel products necessary to rejuvenation and renewal. And too much competition in the world of hospitality as well as the challenges of competition in the room price and diverse consumer desires. Keywords: Marketing Mix and Consumer Decision